The Ideal Concept of Reforming Non-Bank Home Financing: A Justice-Based Approach in Islamic Housing Development - Mustofa, Zaenal; ., Naffi; Winoto, Taufik Pandan; Mashdurohatun, Anis; Yahya , Habib Hasyim Bin Alwi Al Bin; Izhandri , Shandi; Hasan, Ahmed Rabie (Journal of Ecohumanism, 2025)
This study explores the ideal reform of non-bank housing financing within the framework of Islamic housing development, emphasizing a justice-based approach rooted in Sharia philosophies. Conventional housing finance systems often involve riba (interest) and other practices prohibited in Islamic law, leading to a growing demand for Sharia-compliant alternatives. Non-bank Islamic financing models, such as murabaha (cost-plus sales), istishna’ (construction financing), and Ijara wa Iqtina’a (leasing-to-own), offer ethical, transparent, and equitable solutions that eliminate exploitative elements while fostering mutual trust between developers and buyers. These models align with the Islamic philosophies of fairness, transparency, and risk-sharing, addressing both financial and social justice challenges in modern housing. The study highlights the regulatory frameworks, operational strategies, and public awareness required to ensure the effectiveness and sustainability of non-bank Islamic financing. Oversight from bodies like the Financial Services Authority (OJK) and the National Sharia Board (DSN-MUI) is crucial for maintaining compliance and consumer protection. However, challenges such as fraudulent practices, inconsistent implementation of Sharia philosophies, and limited public awareness remain significant barriers. Addressing these challenges through education, stricter enforcement, and technological innovations can enhance transparency, trust, and market reach. In conclusion, the justice-oriented reform of non-bank housing financing represents a transformative approach to addressing housing accessibility and affordability while aligning with ethical and religious values. By fostering inclusivity, equity, and sustainability, this model offers a comprehensive solution for advancing the housing sector in a Sharia-compliant manner.